Els Necrologis de Sarrateix - Masnou i Pratdesaba, Josep M. (Miscel·lània litúrgica catalana, 2013)
In the Royal Library of Copenhaguen is preserved a volume orinigally from the monastery of Santa Maria de Serrateix (Berguedà), consisting in a Martirology with the text of Ado of Vienne, followed by the Regula of saint Benedict and tho Necrologia with the obiti of abbots, monks and other people related to the monastery. The manuscript bears the signature Ny. Klg. Samling 1794. It dates from 11th century. The first Necrologium dates from this century, while the second Necrologium dates from the last quarter of the 14th century. The edition of these texts will allow a better knowledge of the history of the monastery.